2014
DOI: 10.1200/jco.2013.53.5096
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Robot-Assisted and Open Radical Prostatectomy in the Postdissemination Era

Abstract: RARP and ORP have comparable rates of complications and additional cancer therapies, even in the postdissemination era. Although RARP was associated with lower risk of blood transfusions and a slightly shorter length of stay, these benefits do not translate to a decrease in expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 178 publications
(116 citation statements)
references
References 32 publications
7
102
0
7
Order By: Relevance
“…Multi-institutional collaboration between different surgeons from USA and Europe (like Dr Mani Menon, Dr Ashutosh Tewari, Dr Vipul Patel, and Dr Prasanna Sooriakumaran, to name a few) helped to formulate guidelines to achieve the ideal "trifecta" of outcomes (cancer control, potency and continence) [21e24]. Comparison of outcomes of open radical prostatectomy vs. RARP in the post-dissemination era found RARP to have lower 90-d overall rates of wound, respiratory, miscellaneous surgical and medical complications (all p < 0.04), lower postoperative transfusion rates and LOS (both p < 0.001) [25]. RARP resulted in significantly lesser PSM (even in intermediate and high-risk cases) and need for secondary cancer treatment at 6, 12 and 24 months after surgery [26].…”
Section: Evidence Synthesismentioning
confidence: 98%
“…Multi-institutional collaboration between different surgeons from USA and Europe (like Dr Mani Menon, Dr Ashutosh Tewari, Dr Vipul Patel, and Dr Prasanna Sooriakumaran, to name a few) helped to formulate guidelines to achieve the ideal "trifecta" of outcomes (cancer control, potency and continence) [21e24]. Comparison of outcomes of open radical prostatectomy vs. RARP in the post-dissemination era found RARP to have lower 90-d overall rates of wound, respiratory, miscellaneous surgical and medical complications (all p < 0.04), lower postoperative transfusion rates and LOS (both p < 0.001) [25]. RARP resulted in significantly lesser PSM (even in intermediate and high-risk cases) and need for secondary cancer treatment at 6, 12 and 24 months after surgery [26].…”
Section: Evidence Synthesismentioning
confidence: 98%
“…In this context, studies based on several of these data sources have demonstrated that better outcomes might be achieved in high-volume hospitals and/or with more experienced surgeons [21,76]. The evaluation of large cohorts with follow-up data on cancer control has an important role in assessment of the safety and efficacy of PCa treatments [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. Data on health-related quality of life after treatment can also be analyzed.…”
Section: 4mentioning
confidence: 99%
“…Comparative effectiveness of open versus robot-assisted RP [78] Impact of primary ADT on survival in men with clinically localized PCa [119] ADT and the risk of cardiovascular diseases, diabetes, fractures, and acute kidney injury in PCa patients [120,121] Racial disparities and geographic variations in primary treatments among PCa patients [64] Increased use of advanced treatment technologies among patients with low-risk PCa and high risk of non-cancer-related mortality [122] Cost implications of the introduction and widespread adoption of advanced treatment technologies for PCa [103] PCOS: Prostate Cancer Outcomes Study Association between age, race, and comorbidity and the probability of receiving a conservative treatment [67] Comparative effectiveness of radical prostatectomy and radiation therapy [37] 15-yr (long-term) disease-specific functional outcomes after RP and radiotherapy [35] …”
Section: 4mentioning
confidence: 99%
“…The modality of RP is one such factor. While radical retropubic prostatectomy (RRP) has long been the gold standard extirpative therapy for localized prostate cancer, robot-assisted laparoscopic prostatectomy (RALP) is now the predominant surgical treatment approach [14]. RALP has been associated with lower rates of VUAS in multiple national population-based cohorts.…”
Section: Pathophysiologymentioning
confidence: 99%